DAMPAK FAST FOOD ADVERTISING TERHADAP PERILAKU KONSUMTIF ANAK-ANAK - Putri, Inggrid Wiono (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
AbstractChildren is the first target market for fast food company. Fast food advertising is offer several kind of fast food like pizza, fried chicken, hamburger, and many more. They make attractive advertising with many toys and cartoon characters. It’s reacts to children’s tendency to become consumtif to consume fast food which leads them to overweight and obesity problem. This problem can be solved with several tactics from parents, government, and community.Keywords : fastfood, obesity, advertising, children, social media